Democratic Republic of Sao Tome and Principe : Selected Issues and Statistical Appendix. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2006)
The paper reviews the background and the existing institutional framework for oil sector development in Sao Tome and Principe and the challenges faced in implementing transparency rules in all oil-related transactions. It provides a quantitative analysis of the impact of oil sector development on government receipts, spending, and savings, and discusses the determinants of inflation from a statistical point of view. It also shows an analysis of the weak relationship between money growth and inflation.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet